RENEWABLE ENERGY: PHOTOVOLTAICS, AN INTRODUCTION - Iswadi, Iswadi (Universitas Islam Negeri Alauddin Makassar, 2014)
Energy is one of the most hot issue today. Energy consumption has increasing every year around the world but the sources not increasing significanly. Most of the energy source come from coal and oil with decrease every year. However oil and charcoal tends to be distinctive near future since it not renewable. Besides, it is polluting, environmentally harmful and rather expensive. As consequence it is important to explore another renewable energy resources. One good example is solar energy, with using sel phovoltaics technology. Photovoltaics technology have been presented with higher efficiency and low cost in production such as perovskite solar cell.